Sercocephalous latifolius fruit attenuates aluminum chloride-induced oxidative stress and neurotoxicity in Drosophila melanogaster via Drn1 regulation of the IMD signaling pathway - Jamiyu Ayodeji Saliu; Ayobami Matthew Olajuyin; Olaseyo Oluwasola Monday (Elsevier, 2024)
Introduction: Alzheimer disease (AD) is a form of dementia that is a heterogeneous dysfunction of various pathophysiological features. Its morphological characteristics consist of tau aggregates and amyloid plaques. The need for novel therapy in the treatment of AD is required. Hence use of antioxidant, natural products are widely employed for the management and treatment of AD and other neurodegenerative diseases. However, there are still a lot of limitations. Sercocephalous latifolius fruit (SLF) is also known as the African peach and has numerous well-being-endorsing advantages. The Chinese name of SLF is Feizhou hong tao, while the Nigeria (Yoruba) name is Eso Gberesi. It can be grown all over the world. SLF has anti-neurodegenerative properties, however, there is a lack of evidence on their probable molecular mechanism for novel therapeutic properties. Investigations have been conducted on the SFL which shows its medicinal capability, but its ability to attenuate neurodegenerative diseases such as AD is yet to be fully elucidated, and the molecular signally pathways whichmay serve as a therapeutic target. Methods: The modulatory effect of SLF on aluminum chloride-induced neurotoxicity and oxidative stress in Drosophila melanogaster via Defense repressor-1 (Drn1) regulation of immune deficiency (Imd) signaling pathway which may be a useful therapeutic target. D. melanogaster was divided into nine groups. Group 1 served as the basal control as they were fed with a normal basal diet, group 2 served as the negative control as they were fed with Basal Diet and 0.5 ml of aluminum/100 ml distilled water, group 3 served as the positive control as they were fed with basal diet 0.5 ml aluminum chloride/100 ml distilled water and Garlic acid, group 4 and 5 were fed with basal diet and 0.1 and 1 % SLF respectively, group 6 and 7 were fed with basal diet, aluminum chloride and 0.1 and 1.0 % respectively, group 8 and 9 were fed with basal diet, garlic acid, aluminum chloride and 0.1 and 1.0 % SLF respectively. All the groups were left for seven days. The experiment was conducted for 3 months, and the fruit flies were changed every 5 days. Results: Superoxide dismutase, catalase, malondialdehyde, and nitric oxide enzymatic enzymes were assayed. However, the relative expression of Defense repressor-1 was also determined both in vitro and on aluminum-induced neurodegenerative D. melanogaster tissue. A significant increase was observed in the catalase when 0.1 % and 1 % were compared, it could be inferred that the extract proved effective at low concentrations, since its highest antioxidant potential was observed at low concentrations. The results revealed decrease in the activity of malondialdehyde, superoxide dismutase, and nitric oxide biological enzymes in the test groups. There was upregulation of Defense repressor -1 in groups 3, 4, 5, and 6, when compared with the positive and negative control, respectively. Discussion: The result provides evidence that SLF has the potential of upregulating defense repressor genes and modulating biological antioxidant enzymes, which could be further exploited to fully understand the underlying molecular mechanisms responsible for the attenuation of neurotoxicity, oxidative stress, and neurodegenerative diseases such as AD. The results suggest that SLF may be useful as a therapeutic target in AD and other neurodegenerative diseases